2009
DOI: 10.1128/iai.00402-08
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Specificity of Panton-Valentine Leucocidin and Gamma-Hemolysin F Component Binding

Abstract: In this study, the binding of F components of the staphylococcal bicomponent leukotoxins Panton-Valentine leucocidin (LukF-PV) and gamma-hemolysin (HlgB) on polymorphonuclear neutrophils (PMNs), monocytes, and lymphocytes was determined using labeled mutants and flow cytometry. Leukotoxin activity was evaluated by measuring Ca 2؉ entry or pore formation using spectrofluorometry or flow cytometry. Although HlgB had no affinity for cells in the absence of an S component, LukF-PV had high affinity for PMNs (disso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
65
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(67 citation statements)
references
References 22 publications
2
65
0
Order By: Relevance
“…Thus, it has been proposed that, rather than lipids, the leucocidins recognize distinct proteinaceous receptors on the cell surface to target and kill immune cells. Evidence for leucocidin cellular receptors other than membrane lipids is supported by a number of studies which demonstrate specific and saturable binding of the toxins on target cells (173,174,244). In line with this evidence, LukED was recently found to target the chemokine receptor and HIV coreceptor CCR5 to kill inflammatory macrophages, T cells, and dendritic cells (227).…”
Section: Leucocidin Cellular Receptors Dictate Cell and Species Specimentioning
confidence: 59%
See 2 more Smart Citations
“…Thus, it has been proposed that, rather than lipids, the leucocidins recognize distinct proteinaceous receptors on the cell surface to target and kill immune cells. Evidence for leucocidin cellular receptors other than membrane lipids is supported by a number of studies which demonstrate specific and saturable binding of the toxins on target cells (173,174,244). In line with this evidence, LukED was recently found to target the chemokine receptor and HIV coreceptor CCR5 to kill inflammatory macrophages, T cells, and dendritic cells (227).…”
Section: Leucocidin Cellular Receptors Dictate Cell and Species Specimentioning
confidence: 59%
“…In contrast, Morinaga et al demonstrated that their identified "variant" of LukED (later determined to be highly conserved in nearly all sequenced strains of S. aureus) could form active toxins through nonconventional subunit pairings of both PVL and gamma-hemolysin subunits, indicating that the overall diversity of active toxins can become quite large (94). It was further demonstrated by Meyer et al that S subunits efficiently recruit nonconventional F subunits to the surface of host cells (244). For example, HlgB and LukD can be recruited to the surface of cells that have been pretreated with LukS-PV, while LukS-PV or HlgC can recruit LukF-PV to the cell surface (244).…”
Section: Mixed Pores and Toxin Synergismmentioning
confidence: 99%
See 1 more Smart Citation
“…Leukotoxins exert their action by (i) binding of S and F proteins to target cell membranes (21,30); (ii) oligomerization and rapidly increasing intracellular calcium concentrations independently of pore formation and cell activation (12,31); and (iii) reconfiguration of S and F proteins to form functional pores permeable to monovalent cations (32). The capacity of antibodies to inhibit these three steps was tested.…”
Section: Resultsmentioning
confidence: 99%
“…A class S and class F component interact sequentially and synergistically, inducing the activation and permeabilization of target cells and leading to their lysis. LukS-PV and LukF-PV bind to the membrane of human polymorphonuclear cells (PMNs), macrophages, and monocytes to constitute PVL (21).…”
mentioning
confidence: 99%